Imprinting the complex dielectric permittivity of liquids into the spintronic terahertz emission - Balos, Vasileios; Muller, Patrick; Jakob, Gerhard; Klaui, Mathias; Sajadi, Mohsen (Applied Physics Letters, 2021)
We report an approach in time-domain terahertz (THz) spectroscopy for measuring the dielectric response of liquids based on inherent properties of spintronic THz emitters (STEs). The THz electric field radiated from the STE is inversely proportional to the sum of the complex refractive indices of the media surrounding the thin metallic stack of the STE and the stack's conductivity. We demonstrate that by bringing a liquid in contact with the emitter, its complex refractive index and accordingly its dielectric response are imprinted into the radiated electromagnetic field from the emitter. We use water as the test liquid and ascertain its dielectric loss and permittivity in the range of ∼0.3-15 THz.
CRIS-Team Scopus Importer:2023-03-27